Famílias monoparentais: um olhar psicanalítico - Weissmann, Lisette (2008)
This dissertation is the result of the questions raised in the family psychoanalytic practice faced with a significant number of monoparental families affected by similar problems. Such problems consisted of a family crisis situation, which prompted psychological consultation. This is a qualitative study based on the psychoanalytic theory. It includes two main aspects: 1) the clinical cases of monoparental families with problems, and 2) the Theory of the Vinculum Configurations, chosen as the theory that will allow us to understand the clinical vinculum situations. From the theoretical point of view, the investigation includes a review as treated by Psychoanalysis on how the family theme has been considered by various authors. This research is guided by the clinical cases of four monoparental families in vinculum psychoanalytic treatment and by the cultural production of the film The city of men. In it we describe families headed by a woman-mother that constitute a family together with its children from different biological fathers. The study traces the evolution of the father as genitor or provider of spermatozoids up to the concept of the father s function above and beyond the father and mother figures. The children play an important role because they denounce the family as a configuration without a way out and point to the crisis situation that leads them to seek help. They introduce an element of ¨thirdness¨ as they mention the school, the streets, a job, the social environment. We define these types of families as a vinculum configuration made up by a mother and her children. We are not talking about the lack of a father figure but rather about a peculiar conformation that describes the unconscious family structure that supports it. In order to make a thorough study of the concept of family, we include its evolution through history, Brazilian laws, the social sciences and statistics. The clinical cases studied are families of the XXI century; therefore, this research leaves open a number of questions that should be explored in order to promote further theories and to continue developing this subject